“We Come From Different Countries, But We All Have One Earth”: Enhancing Intercultural Competencies Through International and Domestic Student Service Learning - Bletscher, Caitlin; Kate Hellmann (Journal of Interdisciplinary Studies in Education, 2022)
Increasing international enrollments at U.S. universities and the benefits of cross-cultural interactions among domestic and international populations are well known and documented. Intentional, collaborative projects among diverse undergraduate students allow educators to examine intercultural competence and sensitivity development. This study explored two service-learning projects and related interactions among domestic and international undergraduate university students that addressed the global issues of food insecurity and environmental conservation as they relate to the community near the university. The study explored the impact on intercultural competency development through quantitative and qualitative data. The data were merged into overarching interpretations; the results were used to present tangible recommendations for change within the context of internationalization in higher education.